2016
DOI: 10.3174/ajnr.a4746
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Collateral Status by Dynamic CT Angiography in Acute MCA Stroke: Timing of Acquisition and Relationship with Final Infarct Volume

Abstract: BACKGROUND AND PURPOSE: Dynamic CTA is a promising technique for visualization of collateral filling in patients with acute ischemic stroke. Our aim was to describe collateral filling with dynamic CTA and assess the relationship with infarct volume at follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 22 publications
0
20
0
3
Order By: Relevance
“…Relaxation of cerebral vessels during and after an ischemia/reperfusion leads to collateral cerebral blood flow, and thus characterizes an intrinsic strategy of the cerebral vasculature to protect neuroglial structures but also vasculature including endothelium against ischemic injury (Heiss et al, 2001), likewise reported for the heart (Koerselman et al, 2003; Meier et al, 2013). Indeed, cerebral collateral status and sufficiently enlarged calibers of collateral arteries have recently been identified as most relevant for final infarct volume, vasogenic edema formation (with subsequent midline shift), and hence patient outcome (Volny et al, 2016; van den Wijngaard et al, 2016; van der Hoeven et al, 2016). Therefore, patients at risk for stroke with unfortunate collateral status (thus portending poor outcome) could particularly profit from a lithium treatment at low concentrations via a generally improved endothelium-dependent vessel relaxation capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Relaxation of cerebral vessels during and after an ischemia/reperfusion leads to collateral cerebral blood flow, and thus characterizes an intrinsic strategy of the cerebral vasculature to protect neuroglial structures but also vasculature including endothelium against ischemic injury (Heiss et al, 2001), likewise reported for the heart (Koerselman et al, 2003; Meier et al, 2013). Indeed, cerebral collateral status and sufficiently enlarged calibers of collateral arteries have recently been identified as most relevant for final infarct volume, vasogenic edema formation (with subsequent midline shift), and hence patient outcome (Volny et al, 2016; van den Wijngaard et al, 2016; van der Hoeven et al, 2016). Therefore, patients at risk for stroke with unfortunate collateral status (thus portending poor outcome) could particularly profit from a lithium treatment at low concentrations via a generally improved endothelium-dependent vessel relaxation capacity.…”
Section: Discussionmentioning
confidence: 99%
“…A criticism of single-phase CTA in comparison with multiphase CTA is its inherent limitation of evaluating collaterals at a single point in time. Multiphase and dynamic CTA identify additional pial arterial filling on imaging beyond the peak arterial phase 20 21. We postulate, however, that collateral robustness is best evaluated during peak intracranial arterial enhancement and that further opacification of collaterals at more delayed phases (often at 8 and 16 s after peak enhancement) may not effectively assess the capacity of collaterals in sustaining an ischemic penumbra.…”
Section: Discussionmentioning
confidence: 92%
“…Multiphase and dynamic CTA have proved useful in evaluating collaterals, providing temporal information at separate data points 20 21. A criticism of single-phase CTA in comparison with multiphase CTA is its inherent limitation of evaluating collaterals at a single point in time.…”
Section: Discussionmentioning
confidence: 99%
“…aus den Datensätzen der CTPerfusion (CTP) erhoben werden kann. Die Ergebnisse der dynamischen CTA haben eine höhere Korrelation zur resultieren den Infarktgröße und dem klinischen Verlauf [43,44]. In ESCAPE wurde die Mehrzahl der Patienten mit einer multiphasischen (m) CTA untersucht.…”
Section: Kollateralversorgungunclassified